LEGAL ANALYSIS OF THE EVIDENCE ASPECTS IN DEFAMATION CASES - Diki Jan Ramadana Tarigan; T. Riza Zarzani; Mhd. Azhali Siregar (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This study aims to determine the efforts of the Prosecutor's Office in proving criminal charges of defamation based on Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE), from the perspective of the Prosecutor's Office. Perspective of the Criminal Procedure Code (KUHAP). This research is a normative legal research that is prescriptive and applied, and in terms of its objectives it is included in normative or doctrinal legal research. The types of data used include primary data and secondary data. The data collection technique used is library research in the form of books, legal regulations, documents, and others. Data analysis uses a syllogistic method through deductive thinking. Based on the results of the research and discussion, it is concluded that the prosecutor's office in its statement uses evidence in accordance with the provisions of Article 184 of the Criminal Procedure Code concerning valuable evidence in the form of witness statements, expert opinions, letters, instructions, statements from the defendant but does not provide electronic evidence as referred to in Article 5 paragraph (1) and paragraph (2) and Article 44 of the ITE Law concerning electronic evidence. In this case, the prosecution presented evidence, but not proof, in the form of a screenshot of the Facebook page used as the site for the electronic defamation. However, because Indonesia adheres to the Wettelijk negative evidence system, the judge considered the testimony of witnesses, experts, and the defendant sufficient to make a decision.